Pengaruh Instagram, lokasi, dan kemudahan transaksi menggunakan QRIS terhadap keputusan pembelian di Cafe & Warteg Temu Legi Sragen - Linda Ayu Sukrisnawati; Sumaryanto Sumaryanto (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
Consumer behavior has evolved significantly, especially in the way consumers choose products to purchase. Social media platforms like Instagram, along with factors such as location and ease of transactions, have become crucial in influencing purchasing decisions. This study explores the impact of Instagram, location, and the convenience of QRIS transactions on consumer purchasing decisions at Cafe & Warteg Temu Legi in Sragen. The study used a quantitative survey method, distributing questionnaires to 100 participants to gather data. The data were analyzed using multiple linear regression to determine the strength and significance of these variables on consumer behavior. The findings reveal that both Instagram and the location of the cafe have a significant effect on purchasing decisions, highlighting the role of social media and physical store proximity in shaping consumer choices. However, the ease of using QRIS for transactions did not show a significant impact on the purchasing decision, suggesting that while convenience in payment methods is important, other factors such as brand presence and location may play a larger role. This research provides valuable insights for businesses looking to optimize their marketing strategies and improve customer engagement in a rapidly changing retail landscape.